Agronomic characteristics, mineral nutrient content, antioxidant capacity, biochemical composition, and fatty acid profile of Iranian pistachio (Pistacia vera L.) cultivars - Ali Khadivi; Mohammadali Nikoogoftar-Sedghi; Yazgan Tunç (BMC Plant Biology)
Abstract Background Pistachio (Pistacia vera L.) nuts are among the most popular nuts. The pistachio cultivars are tolerant to both drought and salinity, which is why they are extensively grown in the arid, saline, and hot regions of the Middle East, Mediterranean countries, and the United States. Results This study evaluated the agronomic and chemical characteristics of 10 pistachio cultivars (‘Abbasiali’, ‘AhmadAghaei’, ‘Akbari’, ‘Chrook’, ‘Fandoghi’, ‘KalehGhoochi’, ‘Momtaz’, ‘Rezaei’, ‘Sefied’, and ‘Shahpasand’). Total phenolic content, antioxidant capacity, fruit mineral elements, soluble protein content, kernel-oil content, and fatty-acid composition were determined in 60 fruits (20 fruits per replication). Leaf mineral elements were determined in 450 leaves (150 leaves per replication). Significant differences were observed (p < 0.05) among the cultivars, with the coefficient of variation (CV) ranging from 1.03 (unsaturated fatty acids) to 115.16% (early nut splitting). Flower buds varied from 4 (‘AhmadAghaei’) to 7 (‘Momtaz’), and fruit per bunch ranged from 11 (‘Abbasiali’) to 21 (‘Momtaz’). Hull percentage ranged from 36.8 (‘KalehGhoochi’) to 43.1% (‘Chrook’), and nut percentage ranged from 56.3 (‘Chrook’) to 62.4% (‘KalehGhoochi’). Iron content in leaves ranged from 267 (‘Chrook’) to 367 mg/kg (‘Rezaei’), while iron in fruits ranged from 65.72 (‘Fandoghi’) to 81.90 mg/kg (‘Sefied’). Total phenolic content varied from 99.9 (‘Rezaei’) to 184.30 mg/g (‘Fandoghi’), and antioxidant activity ranged from 39.14 (‘Shahpasand’) to 82.89% (‘Sefied’). Oil content ranged from 49.26 (‘Rezaei’) to 67.72% (‘AhmadAghaei’), with oleic acid between 48.4 (‘Rezaei’) and 55.55% (‘KalehGhoochi’). Leaf phosphorus positively correlated with split nut percentage (r = 0.669) and negatively with blank nut percentage (r = -0.734). Fruit potassium strongly correlated with total phenolics (r = 0.917) and oleic acid (r = 0.654). Multiple regression analysis showed that blank nut percentage was negatively correlated with leaf zinc (β = -0.77) and positively with antioxidants (β = 0.77). Early nut splitting showed a negative correlation with antioxidants (β = -0.72). The first three principal components (PC1 = 22.48%, PC2 = 18.15%, PC3 = 15.82%) explained 56.45% of the total variation. Heat map analysis using Ward clustering revealed cultivar groupings based on traits like nutrient content and fatty acid composition. Conclusions The findings obtained in this study allow producers to select the most suitable cultivars for obtaining more efficient and high-quality products. Additionally, choosing cultivars based on environmental factors and market demands contributes to the development of more effective production strategies. The ultimate goal is to provide insights that guide the selection of pistachio cultivars optimized for both agricultural sustainability and market-specific requirements.